Pengaruh Kompensasi Terhadap Kepuasan Kerja Karyawan dengan Motivasi Kerja Sebagai Variabel Intervening (Studi Kasus pada Karyawan UD Setia Jaya) - Wulandari, Restia; Novialumi, Anita (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the effect of compensation on job satisfaction with work motivation as an intervening variable among employees of UD Setia Jaya. The study is based on the importance of implementing an appropriate compensation system to improve employee job satisfaction and encourage higher work motivation. The research aims to analyze the direct effect of compensation on job satisfaction, the effect of compensation on work motivation, the effect of work motivation on job satisfaction, and the indirect effect of compensation on job satisfaction through work motivation as an intervening variable. This study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The sample consisted of 57 employees selected using a saturated sampling technique. The results indicate that compensation has a positive and significant effect on both job satisfaction and work motivation. Furthermore, work motivation has a positive and significant effect on job satisfaction and acts as an intervening variable in the relationship between compensation and job satisfaction. These findings imply that organizations should implement fair and appropriate compensation policies while strengthening employee work motivation to enhance job satisfaction and support organizational performance.